Food intolerance and the food industry - Dean, Taraneh (Woodhead Publishing in food science and technology, 2000)
This unique book has become an indispensable guide for production managers and nutritionists within the food industry as well as providing an authoritative source of information for all those concerned with understanding and managing food intolerance